Anopheles species diversity and potential vectors of zoonotic malaria in Central Kalimantan, Indonesia: Diversitas spesies Anopheles dan vektor potensial malaria zoonotik di Kalimantan Tengah, Indonesia - Permana, Dendi Hadi; Asih, Puji Budi Setia; Suryandari, Dwi Anita; Murhandarwati, Elsa Herdiana; Rozi, Ismail Ekoprayitno; Syahrani, Lepa; Kartapradja, Hannie Dewi Hadyani; Hidayah, Najdah; Bahrani; Irdayanti; Juliawaty, Rita; Coutrier , Elisabeth Farah Novita; Syafruddin, Din (Perhimpunan Entomologi Indonesia, 2025)
Zoonotic malaria is an emerging public health issue in Indonesia, particularly in regions with significant forest cover and frequent interaction between humans and non-human primates. Information regarding the diversity and behaviour of mosquito vectors in these areas is very limited. This study aims to identify the diversity and bionomics of mosquitoes, particularly Anopheles sp., across five ecologically diverse locations in Palangkaraya, Central Kalimantan, to gain an understanding of their potential role in zoonotic malaria transmission. Cross-sectional entomological surveys were conducted during November 2022 (during the rainy season) and October 2024 (at the beginning of the rainy season). Adult mosquitoes were collected using human landing catches (HLC) from 18:00 to 06:00, and larval habitats were surveyed and characterized following the WHO protocol. A total of 1,278 mosquitoes were collected from six genera, with Anopheles letifer Sandosham dominating the Anopheles group (97%), particularly in swampy secondary forests, such as Nyaru Menteng. This species exhibited peak outdoor biting activity shortly after dusk and late at night, posing a greater risk to those outside or in unscreened homes. Larval surveys conducted at 48 sites revealed Anopheles larvae in 27% of habitats, predominantly in swamps (67% positive). Although no significant associations were found with environmental factors, natural and semi-natural water bodies appear key to sustaining vector populations. These findings highlight the ecological flexibility of An. letifer and its potential impact on zoonotic malaria transmission in forest-edge communities. Vector control strategies should include integrated methods, such as larval source management and community-based interventions, particularly in peat swamp regions where interactions between humans and non-human primates are frequent.